(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article explores the phenomenon of phoneme alteration, which refers to the changes that phonemes undergo in a given language or speech community. Phoneme alteration encompasses various phonological processes, including assimilation, dissimilation, insertion, deletion, and substitution, among others. This article delves into the mechanisms and implications of phoneme alteration, providing insights into how these processes contribute to the evolution, variation, and complexity of languages worldwide.